Soil testing: a valuable tool for efficient and economic crop production - Choudhary, Mahipal; Mondal, Tilak; Meena, Vijay Singh (Indian Farming, 2018)
Soil testing is playing an important role in recommending dose of fertilizer inputs required in farm of farmers. From the soil testing, farmers know status of nutrients available in soil, so that they are able to decide future crop patterns as per their suitability without indiscriminate use of chemical fertilizers. With the help of soil testing, soil-health card is also issued to every farmer in every three years for efficient utilization of available nutrients and fertilizer inputs for sustaining agriculture production.